Criminal Law Policy Based on Pancasila Values in the Framework of Strengthening Cyber Security - Akbar Alfianda, Doni (Jurnal Hukum Khaira Ummah, 2025)
Today, threats to the sovereignty of the Indonesian nation are no longer military threats or colonialism over the seizure of a region conventionally, we are entering a digital era where crime enters virtual spaces that can even be said to be borderless. Crime in the digital era is commonly called cybercrime. Cybercrime not only has the potential to damage personal data and information, but can also destroy economic and business activities, infrastructure, and even the stability of a country's national security. Cybercrime is a crime committed by utilizing information and communication technology (ICT). This crime can be said to be an extraordinary crime, therefore in overcoming and preventing it, extraordinary measures are also needed. Prevention and overcoming should be carried out using a criminal law policy approach based on the values of Pancasila. Pancasila is the ideology of the Indonesian nation which is the basis of the state, legal views and legal ideals (rechtidee) of its people in living the life of the nation and state. In addition, Pancasila is also full of respect for humanitarian values and protection of human rights. In such conditions, the existence and relevance of Pancasila in the process of implementing and formulating criminal law policies are not automatically established, but require various efforts to enforce them. National criminal law policies in the context of strengthening and developing cyber security must lead to state goals and be guided by the values of Pancasila as the foundation of the state.